2012
DOI: 10.1021/es203528v
|View full text |Cite
|
Sign up to set email alerts
|

Capping Efficiency of Various Carbonaceous and Mineral Materials for In Situ Remediation of Polychlorinated Dibenzo-p-dioxin and Dibenzofuran Contaminated Marine Sediments: Sediment-to-Water Fluxes and Bioaccumulation in Boxcosm Tests

Abstract: The efficiency of thin-layer capping in reducing sediment-to-water fluxes and bioaccumulation of polychlorinated dibenzo-p-dioxins and dibenzofurans, hexachlorobenzene, and octachlorostyrene was investigated in a boxcosm experiment. The influence of cap thickness (0.5-5 cm) and different cap materials was tested using a three-factor experimental design. The cap materials consisted of a passive material (coarse or fine limestone or a marine clay) and an active material (activated carbon (AC) or kraft lignin) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 36 publications
2
73
0
1
Order By: Relevance
“…Often, polychaetes are the first organisms to recolonize sediments covered by tailings, while the early stages of amphipods and ophiuroids are the last ones to occur (Burd, 2002). Despite an initial rapid colonization, differences in faunal composition and structure may persist for a much longer time and the ecosystem may take decades to recover to its original state (Burd, 2002;Josefsson et al, 2012). For instance, studies of disposal of fine-grained china clay wastes on original, coarser sediment showed that a less diverse fauna was established (Probert, 1975).…”
Section: Recovery Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, polychaetes are the first organisms to recolonize sediments covered by tailings, while the early stages of amphipods and ophiuroids are the last ones to occur (Burd, 2002). Despite an initial rapid colonization, differences in faunal composition and structure may persist for a much longer time and the ecosystem may take decades to recover to its original state (Burd, 2002;Josefsson et al, 2012). For instance, studies of disposal of fine-grained china clay wastes on original, coarser sediment showed that a less diverse fauna was established (Probert, 1975).…”
Section: Recovery Potentialmentioning
confidence: 99%
“…In western Greenland, a BACI (Before After Control Impact) study was conducted over 33 years on the STP of the Black Angel lead and zinc mine in the Maarmorilik fjord system. The results showed that recolonization was slow even 15 years after the cessation of discharges and that, although the abundance of the most opportunistic species was declining, the community was still dominated by opportunistic fauna (Josefsson et al, 2012). The authors related the slow recolonization and recovery of the habitat to the significant levels of metals, mostly lead, in the sediments.…”
Section: Recovery Potentialmentioning
confidence: 99%
“…Sediment could be a gigantic reservoir of various hydrophobic organic chemicals (HOCs) [1,2] [e.g., polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs) and polybrominated diphenyl ethers (PBDEs)], which may stem from a variety of routes (e.g., atmospheric dry/ wet deposition, wastewater discharge, and solid-waste disposal) [3]. When exogenous inputs are effectively controlled, contaminated sediment may become a secondary source of contamination to adjacent aquatic eco-environments [4], releasing once-buried contaminants through molecular diffusion, colloidal transport, particle resuspension, gas ebullition, and bioirrigation/bioturbation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Third, diffusion flux is a key reference index in the framework of remedial actions for contaminated sediment and can be used to evaluate the effectiveness of in-situ remediation. For example, it can be used to select suitable capping materials and layer thickness in capping-amendment programs, and to estimate the magnitudes of reduction in porewater concentrations and releasing fluxes [1]. Consequently, there is an increasing need to quantify diffusion fluxes and to recognize their implications for aquatic quality.…”
Section: Introductionmentioning
confidence: 99%
“…Their physical and chemical properties mean that PCDD/Fs bioaccumulate in aquatic biota, and this is of increasing concern. Lake, river, and marine sediments have often been studied because they can show historical PCDD/F accumulation trends (Yeager et al, 2007;Ren et al, 2009;Josefsson et al, 2012). In contrast, there have been few studies of PCDD/Fs in environmental water because of the large volume of water that is needed for PCDD/F analysis.…”
Section: Introductionmentioning
confidence: 99%